Cultivo de alface em sistemas hidropônicos e concentrações de solução nutritiva - Neta, Helena Maria de Morais (2021)
Although lettuce is traditionally grown in soil, hydroponic techniques are currently being widespread in its production. However, there is a need for further studies, especially regarding nutrient concentrations of the nutrient solution and the hydroponic systems to be used, in order to promote increased crop yield. In view of the above, the objective of this study was to evaluate the effects of hydroponic systems on the production, quality and mineral nutrition of lettuce cultivars subjected to nutrient concentrations in the nutrient solution. The study was conducted in a greenhouse located in the experimental sector of the Department of Agronomic and Forestry Science of the Federal Rural University of the Semi-Arid Region, in Mossoró. A completely randomized design was adopted in a 2 x 2 x 3factorial scheme, with three replicates. Treatments were obtained by combining two lettuce cultivars (Cinderella and Rubinella), two nutrient solutions (Standard nutrient solution (100%) and Diluted nutrient solution (50%)) and three hydroponic cultivation systems (Nutrient Film Technique (NFT), cultivation in substrate (Semi-hydroponic) and Deep Film Technique (DFT or floating)). Plants were harvested at 46 days after emergence and evaluated for variables of production (number of leaves, leaf fresh mass, total dry mass, leaf area, leaf succulence and specific leaf area); quality (titratable acidity, vitamin C, soluble solids and SS/ATT ratio) and mineral nutrition (macronutrients (N, P, K, Mg, Ca) and micronutrients (Fe, Cu, Zn and Mn)). The data obtained were subjected to analysis of variance, decomposing the factors when there was a significant response to the interaction between factors. The cv. Cinderella had higher yields for leaf fresh mass (96.71 g plant-1), total dry mass (4.22 g plant-1), leaf area (3,341.35 cm2 plant-1) and vitamin C (10.04 mg ascorbic acid/100 mL). NFT and floating systems promote the highest values yield, leaf quality and nutrients, especially in the 50% solution, so this solution can be used in these cultivation systems without compromising crop development. The semi-hydroponic system promoted greater plant development, but required the use of a more concentrated nutrient solution (100%)